Distance Effects on Diversity and Abundance of the Flower Visitors of Ocimum kilimandscharicum in the Kakamega Forest Ecosystem. (28th August 2018) - Mandela, Hellen K.; Tsingalia, Mugatsia H.; Gikungu, Mary; Lwande, Wilbur M.
Abstract : Pollination is an important ecosystem service in the maintenance of biodiversity and most importantly in food production. Pollination is on the decline due to habitat loss, exotic species invasions, pollution, overharvesting, and land use changes. This study analyzed the abundance and diversity of flower visitors' of Ocimum kilimandscharicum in Kakamega forest with increasing distance from the forest edge. Data were collected through direct observation and sweep netting. Six study sites were identified along two transects each 2.5 km long and labeled A to F. Distance in metres from the forest edge to each site was A=221, B=72, C=83, D=198, E=113, and F=50. Sampling was done from 7:30 am to 4:00 pm, three days in a week for five months consecutively. Diversity indices of different flower visitors were calculated using the Shannon-Wiener diversity index. One-way analysis of variance was used to compare differences between sites and a two-sample t-test was used to identify mean significant differences in species diversity between the closest and the furthest sites. A total of 645 individuals belonging to 35 species were captured from 4 families. The highest diversity was at site F (H'= 2.38) which was closest to the forest edge and the lowest diversity was from site A (H'=1.44) which was furthest from the forest edge. Distance from the forest edge significantly influenced species diversity (F(3, 20) =14.67, p=0.024). Distance from the forest edge also significantly influenced species abundance between the furthest sites A, D, and E and the nearest sites F, B, and C to the forest edge (t=4.177; p=0.0312) and species richness (t=3.2893; p=0.0187). This study clearly demonstrates that Ocimum kilimandscharicum flower visitors play essential roles in pollination and their higher number of visits translates into higher numbers of seeds set. Many of these pollinators are associated with the forest and hence the need to conserve the Kakamega forest as a source pool for pollinators.